Perbandingan Metode Pengujian Dynamic Cone Penetration (DCP) (Studi Kasus : Ruas Jalan Halmahera Bengkulu) - Sazuatmo Sazuatmo; Aswantu Fajri (MAJALAH TEKNIK SIMES, 2022)
Abstract Comparative evaluation of soil properties is used to determine soil properties in the field. Comparing several methods for grade testing aims to get results that are closest to the original data. Tests using Dynamic Cone Penetration (DCP) are commonly used. However, the method commonly used in Indonesia is in accordance with the 1993 Bina Marga regulation. Meanwhile, the method for testing DCP has many different variations. For this reason, DCP testing was carried out using 12 different methods to obtain test results from each method. The test was carried out at 6 points on the Halmahera Bengkulu road. From the test results, it is found that the largest Plastic Index value is at point A1 which is 98% while the largest CBR is at point B2, which is 62% using the NCDOT method. Of the 12 methods used, no significant differences were found, which means that all of these methods can be used for PI and CBR calculations.